A Guide to Capital Expenditure Analysis (Book). - Schaefer, Hadley P.; Spiller, Earl A. (The Accounting Review, 1974)
Abstract Reviews the book "A Guide to Capital Expenditure Analysis," by Moustafa Abdelsamad